Search for Dark Matter with Very-High-Energy Gamma Rays with Current and Upcoming Ground-Based Observatories - Reis, Igor (2026)
Very-high-energy (VHE; E ≳ 100 GeV) gamma-ray observations provide a powerful laboratory for studying extreme astrophysical environments and physics beyond the Standard Model, with this thesis focusing on indirect dark matter searches using gamma-ray observatories through multiple particle models and detection strategies. A unified statistical framework for VHE analyses is developed, based on a two-dimensional binned likelihood and log-likelihood ratio test statistics, and is used throughout to derive median sensitivities and confidence intervals under realistic instrument response conditions. This framework is applied to dark matter–related scenarios using gamma rays from the inner Galaxy, first probing dark matter–cosmic-ray scattering and deriving sensitivity limits on the dark matter–proton cross section with H.E.S.S.-like, CTAO, LHAASO, and SWGO observations, reaching σpχ ∼ 10−33–10−34 cm2 for keV dark matter masses. A second analysis targets two sub-GeV dark matter candidates—axion-like particles and dark photons—interacting with cosmic rays, with CTAO and SWGO probing couplings down to gαγγ ∼ 0.5–1TeV−1 and kinetic mixing ∈ ∼ 0.05–0.1, extending current gamma-ray and laboratory constraints. Finally, the CTAO sensitivity to dark matter annihilation in the Galactic center is explored within Effective Field Theories and Simplified Models, showing that mediator scales up to M* ∼ 10 TeV and Mmed ∼ 3 TeV can be tested for TeV-scale WIMPs, in complementarity with collider and direct-detection limits. Altogether, these studies demonstrate how a consistent statistical framework combined with next-generation Cherenkov telescopes can address unresolved Galactic center astrophysics and probe a broad range of dark-sector phenomena, highlighting the central role of VHE gamma-ray astronomy in multi-messenger astroparticle physics.